Serbia’s New Growth Agenda : Forging a New Future - World Bank (World Bank, Washington, DC, 2020)
Although current growth rates are improving incomes in Serbia, they are not bringing the country closer to average living standards in the European Union fast enough. To reach European levels of prosperity, Serbia must embrace a new, ambitious agenda for growth. Serbia can become a fast-growing, sophisticated modern economy, driven by its private sector, if it maintains the hard-won gains of macroeconomic stability and advances the transformation in the following seven areas: boosting investment, financing growing firms, skilling workers, raising productivity, expanding exports, enabling business, and unleashing competition. Reforms will at once promote growth and build needed resilience for the coming period and beyond. The challenge is not only economic. It requires courageous, decisive, and bold political commitment as well as strengthening government effectiveness and accountabil